Diode‐based transmission detector for IMRT delivery monitoring: a validation study. (8th September 2016) - Li, Taoran; Wu, Q. Jackie; Matzen, Thomas; Yin, Fang‐Fang; O'Daniel, Jennifer C.
Abstract : The purpose of this work was to evaluate the potential of a new transmission detector for real‐time quality assurance of dynamic‐MLC‐based radiotherapy. The accuracy of detecting dose variation and static/dynamic MLC position deviations was measured, as well as the impact of the device on the radiation field (surface dose, transmission). Measured dose variations agreed with the known variations within 0.3%. The measurement of static and dynamic MLC position deviations matched the known deviations with high accuracy (0.7–1.2 mm). The absorption of the device was minimal ( ∼ 1 % ). The increased surface dose was small (1%–9%) but, when added to existing collimator scatter effects could become significant at large field sizes ( ≥ 30 × 30 cm 2 ). Overall the accuracy and speed of the device show good potential for real‐time quality assurance. PACS number(s): 87.55.Qr